Введение (Вопросы атомной науки и техники, 2003)
This issue is dedicated to the 75th Jubilee of the National Science Center “Kharkov Institute of Physics and Technology” and to the 70th Anniversary of the first in the USSR experiment on atomic nucleus splitting.